The Influence of Toxic Friends in the School Environment on the Learning Process of Student in SMP Negeri 31 Palembang - Putri Oktasela; Taty Fuazi; Erfan Ramadhani (Universitas Muhammadiyah Enrekang, 2024)
Toxic friends are toxic friendships, in human life there will always be a group of friends who are intimidating, rude, disrespectful, always want to win alone and don't want to be blamed, if you feel or experience this then it is an unhealthy form of friendship. . This research was conducted in April-May 2024. This research aims to identify the characteristics of toxic friends, analyze their influence on students' learning processes, and provide recommendations for schools, teachers and parents to help students overcome the influence of toxic friends. It is quantitative with the Research Methodology. What will be used is a quantitative model using a type of correlation research, which seeks to explain the nature of problems that have a causal nature due to the ultimate goal of understanding the causes or influences within the identified variables. From the table data above, tcount > ttable at a confidence level of 0.05 shows that the variance of the two groups being compared is significant with tcount 0.020 < ttable 0.05, so Ho is rejected and Ha is accepted. Thus this research states that there is a significant influence of toxic friends on the process. student learning.